Friendship Conflict, Drinking to Cope, and Alcohol-Related Problems: A Longitudinal Actor-Partner Interdependence Model - Mackinnon, Sean P.; Tougas, Michelle E.; Kehayes, Ivy-Lee L.; Stewart, Sherry H. (Emerging adulthood (Thousand Oaks, CA), 2022)
Drinking to cope with negative affect is a strong predictor of alcohol-related problems. We hypothesized that the association between friendship conflict and alcohol-related problems would be mediated by coping-with-depression motives in emerging adults’ close friendships. We used a 4-wave, 4-month longitudinal self-report survey design measuring friendship conflict, coping motives, and alcohol-related problems from 174 same-sex friendship dyads. Participants were recruited from Nova Scotia, Canada between September 2016 and February 2019. Participants had a mean age of 18.66 (SD = 1.17) and were 66.1% female. Data were analyzed using multilevel structural equation modeling. Coping-with-depression motives mediated the link between conflict and alcohol-related problems at the between- and within-subject levels. Unexpectedly, coping-with-anxiety motives was an additional mediator at the within-subjects level. Interventions for emerging adults’ problem drinking should consider the influence of friendship conflict and its impact on emerging adults’ tendencies to drink to cope with both depression and anxiety. Materials/Syntax: https://osf.io/krs3v/